Analisis Sambungan Balok Kolom Beton Bertulang Menggunakan SNI 2847 2013 dan SNI 2847 2019 - Iskandar Romey Sitompul; Agus Ika Putra; Hifzil Hanif (Jurnal Teknologi dan Rekayasa Sipil, 2024)
Earthquake-resistant reinforced concrete structures must pay attention to the beam-column connection area because beam-column connection is a critical area that needs to be designed really accurately so that it can reduce the energy caused during an earthquake. The beam-column connection is designed to be able to deform during earthquake shocks so as to minimize damage, especially in inelastic areas. This study aims to analyze the design of beam-column connections in irregular structures that refer to SNI 2847 2013 and SNI 2847 2019. In the analysis carried out, designed structure by method SNI 2847 2013 by using earthquake map 2010 and method SNI 2847 2019 by using earthquake map 2017. From the design carried out using of SAP2000 It is known that the size of the columns and beams is sufficient to support the shear forces that occur. There are differences in the results of the review between the planning methods SNI 2847 2013 and SNI 2847 2019. The review carried out on the shear force found that the shear force using the 2013 SNI 2847 regulation with the 2010 earthquake map was 1.149% greater than using the 2017 SNI 2847 regulation with the 2017 earthquake map. The review carried out on the shear stress found that the shear stress using the 2013 SNI 2847 regulation with the 2010 earthquake map was 1.149% greater than using the 2017 SNI 2847 regulation with the 2017 earthquake map. The review of the length of reinforcement distribution at the joint found 640 mm with transverse reinforcement used a diameter of 13 mm and a distance between reinforcement of 150 mm for both regulations, but the SNI 2847 2019 regulation requires standard hooks to be placed in the core restrained column.